2011
DOI: 10.1177/0269881111408961
|View full text |Cite
|
Sign up to set email alerts
|

A clozapine-like effect of cyproheptadine on progressive ratio schedule performance

Abstract: Abstract. The atypical antipsychotic drug clozapine has multiple pharmacological actions, some of which, including 5-hydroxytryptamine (5-HT 2 ) and histamine (H 1 ) receptor antagonist effects, are shared by the non-selective 5-HT receptor antagonist cyproheptadine. Atypical antipsychotics have a characteristic profile of action on operant behaviour maintained by progressive-ratio schedules, as revealed by Killeen"s (1994) mathematical model of scheduled controlled behaviour. These drugs increase the value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
20
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 69 publications
9
20
0
Order By: Relevance
“… Valencia-Torres et al (2014) found that diabetes induced by systemic treatment with streptozotocin was associated with a reduction of a , consistent with an antihedonic effect of this treatment ( Nefs et al, 2012 ). D 1 and D 2 dopamine receptor antagonists also reduce a , consistent with the purported antihedonic effect of these drugs ( Olarte-Sánchez et al, 2012 : data re-analysed by Bradshaw and Killeen, 2012; Olarte-Sánchez et al, 2013 ). Some drugs with known sedative properties, including clozapine and cyproheptadine, have been found to increase the response-time parameter δ ( Olarte-Sánchez et al, 2012 : data re-analysed by Bradshaw and Killeen, 2012 ).…”
Section: Introductionsupporting
confidence: 55%
See 3 more Smart Citations
“… Valencia-Torres et al (2014) found that diabetes induced by systemic treatment with streptozotocin was associated with a reduction of a , consistent with an antihedonic effect of this treatment ( Nefs et al, 2012 ). D 1 and D 2 dopamine receptor antagonists also reduce a , consistent with the purported antihedonic effect of these drugs ( Olarte-Sánchez et al, 2012 : data re-analysed by Bradshaw and Killeen, 2012; Olarte-Sánchez et al, 2013 ). Some drugs with known sedative properties, including clozapine and cyproheptadine, have been found to increase the response-time parameter δ ( Olarte-Sánchez et al, 2012 : data re-analysed by Bradshaw and Killeen, 2012 ).…”
Section: Introductionsupporting
confidence: 55%
“…It was injected intraperitoneally (2.5 ml kg −1 ; 25-gauge needle) 30 min before the start of the experimental session. The doses of THC were selected on the basis of previous experience of the effect of this drug on performance on the progressive-ratio schedule ( Olarte-Sánchez et al, 2012 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The breakpoint was defined as the last ratio completed before 5 min elapsed without any responding or, when this criterion was not met within the session, the highest completed ratio (Olarte-Sánchez et al , 2012). The mathematical model (Bradshaw and Killeen, 2012) used to analyse PR performance comprises three key equations.…”
Section: Methodsmentioning
confidence: 99%